An adaptive multilingual interface for tourism information. (5th January 2005) - Berger, Helmut; Dittenbach, Michael; Merkl, Dieter
We have developed a natural language query interface for Tiscover, the largest Austrian web-based tourism platform. For a period of ten days, this interface was made publicly available by means of an advertisement and a hyperlink on Tiscover's homepage. In this paper, we will describe the results and our insights from analysing the natural language queries collected during this field trial. This analysis shows how users formulate queries when their imagination is not limited by conventional search interfaces with structured forms consisting of check boxes, radio buttons and special-purpose text fields. The results of this field trial are thus valuable indicators for determining the direction the web-based tourism information system should be extended into, in order to better serve the customers.